The Effect of Sample Density of Mixed Husk and Bran on Reflection and Transmission Coefficient of Acoustic Waves - Abdjul, Tirtawaty; Kurniasari, Septiana; Katili, Nancy; Payu, Citron Supu (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2022)
Noise is a sound that is not desired because it is not in accordance with the context of activity, space, and time so it can cause disturbances to comfort and even human health. Twoof the basic ingredients of a silencer are husk and bran. This research aimed to determine the effect and model of the relationship of the density of the sample mixture of husks and bran on acoustic waves' reflection coefficient and transmission coefficient. The method used in this research is experimental, using a mixture of husk and bran samples whose density consists of 5 variations. The results showed that the husk and bran mixture's sample density strongly affected the reflection coefficient (r = 0.947 to r = 0.966) and the transmission coefficient (r = -0.962 to r = -0.999). These resultsshow that the greater the sample density of the husk and bran mixture, the greater the absorption intensity fraction produced. Statistically, the level of influence is indicated by the correlation coefficient, whose value is around r = 0.95 to r = 0.99. Based on the results, the reflection and transmission coefficients are influenced by the density of the mixture of husk and bran samples.